(untitled) (Educação e Pesquisa, 2020)
The article analyzes the contributions of a didactic sequence regarding water in promoting scientific literacy in the early years. A pedagogical intervention research was developed with 24 students from Elemetary public school in Araucária/PR, during the second semester of 2016, involving the implementation of a didactic sequence based on the three pedagogical moments and the elaboration of conceptual maps. A semi-structured interview was conducted with the students, using the concept maps built as a base, so that they could explain the knowledge acquired during the didactic sequence, supporting the analysis of the presence of indicators of scientific literacy. The results showed that the implementation of the didactic sequence materialized the necessary skills to be scientifically literate, showing that the school has the important role of enabling access to scientific knowledge, being fundamental that it provide a formative process from an early age, aiming to form critical and conscious citizens. who understand scientific language and know how to use it more actively in society. We found that the didactic sequence developed skills necessary for the promotion of scientific literacy in that it provided students with the experience of situations in which they had to position themselves, putting in check their previous conceptions about the studied themes, demonstrate the appropriation of several concepts. evidencing the construction of knowledge. In order for the student to become a critical citizen, aware of society and take a stand on processes and innovations that affect him/her daily, new actions and didactic resources are needed to help increase scientific literacy.